Confined wetting of water on CNT web patterned surfaces - Zhao, Yugang (2017)
We report the formation of a thin liquid film of pre-determined shape that is achieved through wetting of water on a silicon surface patterned with aligned carbon nanotube arrays or CNT webs. We measured the profiles of liquid films on two types of silicon substrate surfaces (namely, with and without a patterned CNT web) using monochrome interferometry. We found that the CNT web patterned surface produces a much thinner liquid film with a well-controlled shape due to the roughness-induced wetting enhancement on the CNT web and the anchoring effect of contact lines at morphological edges. We further used a thermodynamic surface energy based model to interpret our experimental observations and to elucidate the underlying mechanism of wetting enhancement induced by the CNT web. Our study provides a promising approach for forming thin liquid films of controllable pre-determined shape that has numerous potential applications.